China Pakistan Economic Corridor (CPEC): Opportunities and Challenges for Pakistan - Shahida Raz Bhutto, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
China Pakistan Economic Corridor (CPEC), under the Belt and Road Initiative (BRI), is a corridor that features a 2,000-kilometer long pipeline, along with rail and road connections. Pakistan and China decided to construct it to develop economy and promote peace and prosperity in the region. This paper aims to explore the numerous internal and external obstacles and challenges faced by Government of Pakistan in carrying out this multimillion-dollar project. The paper highlights that the project will boost trade and the economy, fortify regional connectivity, resolve energy challenges, build infrastructure and foster interpersonal relationships between the two states. The study is qualitative in nature. Data is collected through secondary sources and analyzed using the content analysis method. The realist theory provides an understanding of geopolitical rivalry, external pressures and internal challenges with respect to state’s security-first approach and how these phenomena shape the trajectory of the project. While CPEC has provided economic opportunities, it has also left Pakistan in a web of external competition and internal unrest. This reaffirms the realist approach that even seemingly economic projects are not free from power politics and security concerns.